2017
DOI: 10.3390/en10040557
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Hard Roofs in Solid Backfill Coal Mining Using Physical Models

Abstract: Solid backfill coal mining technology has been widely applied in coal seams that are at risk of hard roof. Using actual measured strain-stress curves of the backfill body and the similarity theory, this study designed and employed four experimental models for physical simulation, corresponding to roof-controlled backfilling ratios of 0%, 40%, 82.5% and 97% using the geological conditions of Face No. 6304 in the Jining No. 3 coal mine-a solid backfill coal mining face under a hard roof. A non-contact strain mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Zhang et al [38] demonstrated that the hard-roof-induced face burst can be reduced effectively by preventing the roof-caving movement through solid backfilling mining method. Zhou and Li et al [39,40] determined the reasonable backfilling ratio to control the hard roof deformation and reduce the mining abutment stress. He et al [41] analyzed the rockburst prevention by cutting the hard roof directionally in advance under mechanical behaviors of the deep-hole directional fracturing of hard roof.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [38] demonstrated that the hard-roof-induced face burst can be reduced effectively by preventing the roof-caving movement through solid backfilling mining method. Zhou and Li et al [39,40] determined the reasonable backfilling ratio to control the hard roof deformation and reduce the mining abutment stress. He et al [41] analyzed the rockburst prevention by cutting the hard roof directionally in advance under mechanical behaviors of the deep-hole directional fracturing of hard roof.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the failure of the coal pillars left during or after mining may cause security issues and ground subsidence [16][17][18][19][20]. The backfill mining method uses filling bodies to replace coal pillars to support the roof to control the movement and deformation of overlying strata, and therefore to reduce the ground subsidence [21][22][23]. Currently, the backfill mining method has been widely employed in longwall mining; however, it is still experiencing limits in applications.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al developed a comprehensive mechanized filling coal mining technology which could control the movement of rock stratum and surface subsidence by controlling the backfill rate in goaf [6][7][8][9]. Based on the systematic study of the compaction of waste rock backfilling materials and time correlation, Zhang et al [10][11][12][13][14][15][16] presented an equivalent height model for analyzing the law of mining pressure by filling the goaf with waste rocks. He also obtained the supporting strength in fully mechanized mining and the correction coefficient of filling mining with traditional fully mechanized support strength.…”
Section: Introductionmentioning
confidence: 99%